Digitalisasi Digitalisasi Desa: Mewujudkan Desa Ciparasi, Lebak Banten Yang Cerdas dan Berliterasi Digital - Musa, Musa; Ardiyansyah, Dimas; Febrian, Ari; Putra, Fajar Setyaning Dwi (Universitas Negeri Jakarta, 2025)
Ciparasi village, Sobang district, Lebak Regency Banten Province still face challenges such as limited infrastructure and low digital literacy. Among them are the uneven Internet infrastructure and the lack of computer hardware in some regions obstructing the optimization of technology. Low digital literacy, especially among older citizens, requires more intensive educational programmes. Therefore, this community service program aims to digitize villages in order to support the quality of life of citizens through administrative efficiency, improved technological infrastructure, training and education programmes, and digital services applications implemented. Through this program, the efficiency of village administration is increased and public services are made faster and more transparent. The improvement in the quality of life of villagers is reflected in the ease of access to health services and education through digital applications. In conclusion, digitization of villages brings many tangible benefits but requires collaborative efforts between governments, technology service providers, and the public to address the challenges. Comprehensive training and education programmes must continue to be implemented to ensure that the whole layer of society can make optimal use of digital technology.